NOTICIAS DE LA BIBLIOTECA DEL CHANTRE DE TERUEL JOAQUÍN IBÁÑEZ GARCÍA - José María de Jaime Lorén (Cuadernos de Ilustración y Romanticismo, 2017)
We have provided new news from various archives about the precentor of Teruel, Joaquín Ibáñez García, and about his valuable book collection acquired as he died by the Real Biblioteca. Also about the library of his step-brother, Marcos Ibáñez Aldea, architect who built the city of New Guatemala and took to Central America the Neoclassical style.